2012
DOI: 10.1080/07315724.2012.10720006
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Depresses Fat Metabolism in Older Individuals

Abstract: Although statin therapy normalizes blood lipoproteins, it reduced fat metabolism in older individuals, which cannot be a result of lower availability from blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In the present study, the fat oxidation rate was similar between simvastatin-treated patients and control subjects. This is in line with the studies of short treatment (5 days–8 weeks) [ 15 , 16 ], but not those of longer treatment [ 17 19 ]. However, in the long-term studies, it is possible that a different plasma lipid profile [ 17 , 19 ], VO 2 max, or age [ 18 ] between the treatment and control groups may have caused the reported difference in fat oxidation rate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the fat oxidation rate was similar between simvastatin-treated patients and control subjects. This is in line with the studies of short treatment (5 days–8 weeks) [ 15 , 16 ], but not those of longer treatment [ 17 19 ]. However, in the long-term studies, it is possible that a different plasma lipid profile [ 17 , 19 ], VO 2 max, or age [ 18 ] between the treatment and control groups may have caused the reported difference in fat oxidation rate.…”
Section: Discussionsupporting
confidence: 89%
“…In the light of the study by Phillips et al [ 4 ] and the preclinical data by Langhi et al [ 5 ], the question arises as to whether chronic simvastatin use changes fatty acid storage and oxidation in humans. The literature on the effect of statins on FA oxidation rate in humans is conflicting with studies reporting either no effect [ 15 , 16 ] or simvastatin-induced impaired fat oxidation [ 17 20 ]. One explanation for controversy could be that the studies that report no effect of statins on fat oxidation (FO) only use treatments of shorter duration (5 days to 8 weeks) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this could also be due to a lack of NADPH, because the following NADPH-producing reactions are downregulated by statins: 1) glycolysis, including the NADPH-producing pentose-phosphate cycle as well as the KREBS or tricarbonic acid cycle (39) , 2) the fatty acid oxidation (40) , 3) the OCM, which was identified as a major producer of NADPH by quantitative flux analysis (41) , and 4) TYMS , which is among the most downregulated genes analyzed in our transcriptomic study, is known to convert dUMP to dTMP in the presence of NADPH and serine (42) . Thus, a lack of NADPH could be responsible for the downregulation of this gene in responsive cell lines ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other conflicting results include reports in humans of increased resting RER with statins, indicating a possible shift from fat to CHO metabolism [13,35]. A 12-week aerobic training study measured a greater increase in VO2max in a -statin, compared with +statin group.…”
Section: Discussionmentioning
confidence: 99%
“…The available research in patients undergoing exercise has produced conflicting results, with studies confounded by the co-administration of a kaleidoscope of other cholesterol-lowering agents, or with β-blockers, which inhibit the release of FFA from adipose tissue and complicate the interpretation of the data [11,12]. One study in patients has reported reduced fat oxidation with atorvastatin, during lower-intensity exercise [13]. Patients have also self-reported increased fatigue with exertion after taking simvastatin for a period of 6 months [14].…”
Section: Introductionmentioning
confidence: 99%